NQPC-09 PROGNOSIS AND DELAYED COMPLICATIONS OF MEDULLOBLASTOMA IN KOBE CHILDREN'S HOSPITAL. (16th December 2019) - Kawamura, Atsufumi; Koyama, Junji; Akutsu, Nobuyuki; Yamanishi, Shunsuke
Abstract: Medulloblastoma is the most common pediatric malignant tumor and about 84.2% of cases are under 15 years old. With a current combined-modality approach that includes surgical approach, chemotherapy and radiation therapy, 5 year-survival rates have become 70–85% and also the so-called long-term survivors have increased in our country. This report reviews the prognosis and delayed complications of medulloblastoma in our institute. Cases were 14 boys and 11 girls from January, 2010 to May 2019. Mean age was 6.1 years old (4 months to 14 years old). 18 cases receiver gross total removal and 12 cases were high risk group. Exclude recent 4 cases, 15 cases have indicated complete reaction though 6 cases had relapsed or new tumor. The results are that 5 year-survival rates in our institute is 86.7%, but 4 cases had neuro-psychological complications. 5 cases suffered from endocrinal disorders which were not confirmed after the end of all treatments. 2 secondary cancer had appeared 5 and 8 years after the first treatments. The more the survivor in medulloblastoma cases increase, neurosurgeons have to consider long term follow up more than 5 years and pay more attention to support activity of daily life of these patients.